Pengembangan E-Modul dengan Aplikasi Canva dan Flipbook Pada Pembelajaran Ekonomi - Rani Sofya; Suciyana Febri Adzkia (Universitas Negeri Padang, 2023)
The purpose of this research is to 1) Develop e-module using the Canva Design and Flipbook applications in economic learning subjects as a feasible learning media. 2) Knowing how the feasibility of e-module. 3) Knowing how the practicality of e-module for economic learning media at SMA N 1 Gunung Talang. This research method is a research and development method (Research and Development) with the Thiagarajan development model known as 4-D which consists of 4 stages, namely (Define, Design, Develop and Disseminate) but the research is limited to the development stage only (Develop). E-module products are possible to produce based on the approval of content, media, and language experts.